2004
DOI: 10.21273/jashs.129.3.0439
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Partitioning, and Storage of Fertilizer Nitrogen in Red Raspberry as Affected by Rate and Timing of Application

Abstract: The effects of 15N-labeled fertilizer applied to mature summer-bearing red raspberry (Rubus idaeus L. `Meeker') plants were measured over 2 years. Four nitrogen (N) treatments were applied: singularly at 0, 40, or 80 kg·ha-1 of N in early spring (budbreak), or split with 40 kg·ha-1 of N (unlabeled) applied at budbreak and 40 kg·ha-1 of N (15N-depleted) applied eight weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
6
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 22 publications
6
68
6
1
Order By: Relevance
“…Other perennial fruit crops also have relatively low rates of fertilizer N uptake. Raspberries, with a perennial rootstock and a biennial top, derived 13-36% of N from fertilizer (Rempel et al 2004). In a study with perennial pecan trees, 28% of 15 N labeled fertilizer was found in the plant, 24% in the soil, and 48% was lost to the environment (Rey et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other perennial fruit crops also have relatively low rates of fertilizer N uptake. Raspberries, with a perennial rootstock and a biennial top, derived 13-36% of N from fertilizer (Rempel et al 2004). In a study with perennial pecan trees, 28% of 15 N labeled fertilizer was found in the plant, 24% in the soil, and 48% was lost to the environment (Rey et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Biomass of fruiting clusters (Dean et al 2000) and of whole floricanes (Kowalenko 2003) were used as indices of relative berry yield. Primocane length and diameter and mean primocane dry weight were used as indices of primocane vigor (Zebarth, Freyman, and Kowalenko 1993;Dean et al 2000;Rempel, Strik, and Righetti 2004). Fruiting cluster and whole floricane N concentration and N accumulation at onset of commercial berry harvest, dormant floricane N concentration, and primocane N concentration were used as indices of crop N status.…”
Section: Methodsmentioning
confidence: 99%
“…In Oregon, Chaplin and Martin (1980) found no significant effect of N fertilization rate on yield of red raspberry over a 5-year period, whereas Rempel, Strik, and Righetti (2004) measured a yield response in the second year of a 2-year experiment. In Scotland, N fertilization increased yield in the first 2 cropping years, had no effect on yield in the subsequent 3 years, and decreased yield in the final 2 years, suggesting that N requirements and consequently yield response to N fertilization may vary depending on the age of the crop (Lawson and Waister 1972).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, the fertilization practices are also important in terms of quantity and timing [37], and this can greatly affect nitrate leaching. For example, an important rainfall Fig.…”
Section: The Growing Seasonmentioning
confidence: 99%